Nexus Between Macroeconomic Indicators and Stock Market Composite Index in ASEAN-4 - Aung San, Lwin (UNIMAS, 2024)
The ASEAN-4 countries: Malaysia, Singapore, Thailand and Indonesia, have been experiencing a significant growth in their stock markets over the past 30 years. This growth has been largely attributed to macroeconomic indicators. To make well-informed decisions while investing in stocks from these countries, investors need to comprehend the relationship between the macroeconomic indicators and stock market composite index. The purpose of this study is to investigate the nexus between the macroeconomic indicators including exchange rate, GDP (Gross Domestic Product), inflation and real interest rates, and the stock market composite index in the ASEAN-4 countries comprising Malaysia, Singapore, Thailand, and Indonesia. Quantitative method of this study is to investigate the long and short run associations of macroeconomic indicators and stock market composite index of the ASEAN-4 countries; the empirical analysis methods are applied based on yearly data of five time-series variables cover the sample period spinning over for 30 years, from 1988 to 2019; to analyse the nexus between macroeconomic indicators such as exchange rate, gross domestic product, inflation and real interest rates, and their causal effects on the stock market composite index of each ASEAN-4 country by constructing the separate VECM model for each country. The comprehensive analysis methods for each country are the unit root test, cointegration test, three types of VECM tests (Error Correction t-test, VECM and Granger causality test), Wald test for short run joint causality effect, CUSUM of square test for model stability, Chow test structural breakpoint shock checking. Moreover, the variance decomposition test is comprised for finding the sequence of exogeneity of significant innovative shocks among the variables of each country model. The VECM models highlight that there is a significant nexus between macroeconomic variables and stock market composite index in each ASEAN-4 country; the common findings indicate that exchange rate, inflation rate, real interest rate and GDP are the common macroeconomic indicators that have significant long run and short run causality effects on stock market composite index and vice versa. The results of variance decomposition also indicate that the sequence of common leading indicators is exchange rates, inflation rate and real interest rate which are to be synchronised among the ASEAN-4. This study contributes theoretical implications regarding the research area in financial economic as evidence to highlight the nexus between the key macroeconomic indicators and the stock market composite index; as a managerial contribution for the policymakers and investors for their respective national policy making and cross border trading and investment in ASEAN-4.